(untitled) (Global Scientific Review, 2024)
This article highlights the issues of improving the effectiveness of geography education, pedagogical skills of the geography teacher, and organization of extracurricular activities in the development of students’ creativity in geography education. Also, the technology of organizing extracurricular activities, recommendations on the effective organization of student activities are presented.